Influence of PSC Changes in The Upstream Sector From Cost Recovery System into Gross Split Towards The Obligation to Pay Land and Building Tax - Irine Handika Ikasari (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2019)
AbstractThe scheme of profit sharing contracts has been significantly changed due to the enactment of Ministerial Regulation of Energy and Mineral Resources No. 8/2017 concerning the Gross Split Revenue Sharing Contract on January 16, 2017.This research focused on: First, the relationship between the change of PSC Cost Recovery form to PSC Gross Split with the mechanism of Administration of Land and Building Tax and its addressat; and Second relationship between change of PSC Cost Recovery form PSC Gross Split with procedure of Land and Building Tax calculation at exploration and exploitation stage.IntisariSkema kontrak bagi hasil mengalami perubahan yang sangat signifikan akibat diundangkannya Peraturan Menteri ESDM No. 8/2017 Tentang Kontrak Bagi Hasil Gross Split pada tanggal 16 Januari 2017. Penelitian ini difokuskan pada: Pertama, hubungan antara perubahan bentuk PSC Cost Recovery menjadi PSC Gross Split dengan mekanisme penatausahaan Pajak Bumi dan Bangunan dan addressat-nya; dan Kedua hubungan antara perubahan bentuk PSC Cost Recovery menjadi PSC Gross Split dengan tata cara perhitungan PBB pada tahap eksplorasi dan eksploitasi.